Efektivitas Pengendalian Intern Penerimaan Kas Dari Pasien Rawat Inap: Studi Kasus pada Rumah Sakit Panti Rini - Damar Prasetyaaji; Muhamad Rifandi (CV. ULIL ALBAB CORP, 2023)
The objectives of the research carried out by the researcher were 1) to identify whether the components of internal control for Inpatients Cash Receipts which were implemented at the Panti Rini Hospital, 2) to identify whether the internal control for Inpatients Cash Receipts at the Panti Rini Hospital is effective. In this study, a qualitative method was implemented. The qualitative data was collected through interviews, observation, and documentation; then be evaluated and presented descriptively. The results also resemble effectiveness in the Internal Control for Cash Receipts from Inpatients at the Panti Rini Hospital.